السجع في اللغة العربية واللغة الإندونيسية دراسة تقابلية تطبيقية - Alaina Almardhiyah; Arif Taufikurrahman (Rayah Al-Islam, 2020)
This study aimed at knowing the Arabic and Indonesian temptations and revealing similarities and differences between them in terms of definition, conditions, characteristics, and divisions, and its predicts are to predict expected problems through the study of the Arabic prostrate, then draw to the results of the corresponding study to prepare appropriate study materials in the education of the prostrate for Indonesian students at the university level. This study followed the descriptive and analytical approach to find out the characteristics that the Sajā contained in both languages. It also used the cross-analytical approach to compare their systems and extract their similarities and differences. This study reached three results, the first of which is the similarities and differences between the Arabic and Indonesian braves that were exposed. The second is problems that arise based on the differences between them. And the last, applications from the results of the opposite study, such as making use of them to form some types of prose and display them when explaining, and drawing them into to design a study unit to teach al-Sajā for the university stage.